Health Index for Tuberculosis Patients on Family Ability Based on Self-Care - Suprajitno Suprajitno; Sri Mugianti; Abdulateef Al-Hadeethi (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2022)
Introduction: The health index of a patient of tuberculosis can be calculated using variables obtained from the indicators that were developed based on the sufferer and family's behaviors while preventing the disease based on the nursing theory of self-care. It is expected that a family must be able to treat infected members at home properly using technical treatment. Therefore, this study aims to construct a health index formula for tuberculosis patients.Methods: A cross-sectional design was used and further divided into two phases. The first is focus group discussions, which were carried out between tuberculosis treatment holders, Puskesmas nurses, and researchers to develop measurement instrument indicators. A survey was performed in the second phase for patients who were registered and treated in Public Health Center at Blitar, East Java, Indonesia. The 141 responses obtained were selected using a simple random sampling technique. The data were collected using a questionnaire developed from the focus group discussions and then analyzed using factor analysis.Results: A Goodness of Fit Index (GFI) value of 0.98 was recorded along with composite value reliability of 53%. The formula of Health index obtained from the analysis was (0.238* Home environment) + (0.226* Family prevention efforts) – (0.659* Coughing habits of patients) + (0.250* Impact of treatment). The index was then calculated in four categories, namely low, enough, good, very good.Conclusion: So, the health index formula of tuberculosis patients is illustrated as Health Index=0.238*X1+0.226*X2-0.659*X3+0.250*X4.